Mechanistic study of CO oxidation by N2O over Ag7Au6cluster investigated by DFT methods - Yutthana Wongnongwa (2018)
ï¿½ 2017 Elsevier B.V. The potential of Ag 7 Au 6 alloy nanocluster to be a catalyst for the oxidation of CO by N 2 O has been examined by density functional theory calculations. In the first mechanistic step, an N 2 O molecule decomposes at the Ag facet site of the Ag 7 Au 6 cluster, yielding an N 2 molecule and an Ag 7 Au 6 [sbnd]O intermediate. In the second step, the Ag 7 Au 6 ‐O intermediate readily reacts with CO to form CO 2 . The product CO 2 desorbs easily from the active Ag 7 Au 6 site, thus avoiding catalyst poisoning. The potential energy surfaces of the doublet- and quartet-states have been systematically elucidated. There is no spin crossing found for the entire reaction and the results show that the reaction preferably follows the doublet state pathway. The activation Gibbs free energy barrier for the first and second steps are 24.6 a nd 10.6 kcal/mol, respectively, while the Gibbs free energy of the overall reaction is −81.2 kcal/mol. The results reveal that this catalyzed reaction is both thermodynamically and kinetically favorable. Therefore, the Ag 7 Au 6 nanocluster is predicted to be a promising and highly active catalyst for conversion of CO and N 2 O pollutants to non-harmful products under ambient conditions.